PENGARUH PENERAPAN SYSTEM APPLICATIONS AND PRODUCTS IN DATA PROCESSING TERHADAP KINERJA MANAJERIAL (STUDI KASUS PT PUPUK ISKANDAR MUDA LHOKSEUMAWE) - Mulia Andirfa; Rizka (Jurnal Penelitian Ekonomi Akuntansi, 2020)
This study aims to determine the effect of the application of System Application and Product in Data Processing on managerial performance at PT Pupuk Iskandar Muda Lhokseumawe, the use of accounting information system information technology is very important in its role in a company, Enterprise Resource Planning with its Software Application Systems and Products in Data Processing widely used by manufacturing companies that can improve the efficiency of the accounting information system that results in effective and efficient management performance, this study uses a descriptive approach, quantitative associative form, using primary data, sampling techniques used probability sampling with random sampling methods with the sample object is 55 employees of PT Pupuk Iskandar Muda. The results showed that the application of System Application and Product in Data Processing had a positive and significant effect on managerial performance at PT Pupuk Iskandar Muda, this was seen from the results of tcount> ttable (2.585> 1.67) and the coefficient of determination of 63.2% which shows that managerial performance is influenced by the application of System Applications and Products in data processing, while 36.8% is influenced by other factors outside this study.